The Effect Of Good Corporate Governance, Work Life Balance, Talent Management And Person Organization Fit On Employee Performance At The Planning, Research And Development Agency Of Bukittinggi City - Robby Dharma; Lestari Gusnawati (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Putra Indonesia YPTK, 2022)
The purpose of this research journal is to find out how much